Conserved B-cell epitope identification of envelope glycoprotein (GP120) HIV-1 to develop multi-strain vaccine candidate through bioinformatics approach - Kharisma, Viol Dhea; Ansori, Arif Nur Muhammad; Posa, Gabrielle Ann Villar; Rizky, Wahyu Choirur; Permana, Sofy; Parikesit, Arli Aditya (Jurnal Teknologi Laboratorium, 2021)
Acquired immune deficiency syndrome (AIDS) has been identified from US patients since 1981. AIDS is caused by infection with the human immunodeficiency virus type 1 (HIV-1) which is a retrovirus. HIV-1 gp120 can be recognized by the immune system because it is located outside the virion. The conserved region is identified in gp120, and it is recognized by an immune cell which then initiates specific immune responses, viral mutation escape, and increase vaccine protection coverage, a benefit derived from the conserved region-based vaccine design. However, previous researchers have little knowledge on this conserved region as a target for vaccine design. This paper explains how the conserved region of gp120 HIV-1 is a major target for vaccine design through a bioinformatics approach. The conserved region from gp120 was explored as a vaccine design target with a bioinformatics tool that consists of B-cell epitope mapping, vaccine properties, molecular docking, and dynamic simulation. The peptide vaccine candidate of B5 with the gp120 HIV-1 conserved region was found to provoke B-cell activation through a direct pathway, produce specific antibody, and increase protection from multi-strain viral infection.